Do Persons Living with HIV Continue to Fill Prescriptions for Antiretroviral Drugs during a Gap in Care? Analysis of a Large Commercial Claims Database. (November 2017) - Byrd, Kathy K.; Bush, Tim; Gardner, Lytt I.
The significance of a gap in HIV care depends, at least partially, on whether patients continue to fill prescriptions for antiretroviral (ARV) drugs during the gap in care. We used a billing claims database to determine the proportion of persons who filled ≥1 prescription for ARV drugs during a gap in care (no clinic visit in >6 months). Persons were stratified into 3 groups: "never" (prescriptions never filled), "sometimes" (prescriptions filled >0%-<100% of months), and "always" (prescriptions filled monthly). Logistic regression analyses were conducted to determine factors associated with "never" filling ARV drugs. Of 14 308 persons, 69% (n = 9817), 13% (n = 1928), and 18% (n = 2563) "never, " "sometimes, " and "always" filled ARV drugs during the gap in care. Persons aged 18 to 29 years (odds ratio [OR] = 1.56, 95% confidence interval [CI] 1.39-1.74), women (OR = 1.67, CI 1.52-1.83), and persons from the Northeast region of the United States (OR = 1.86, CI 1.69-2.03) were more likely to never fill ARV drugs than persons aged ≥30 years, men, and persons outside the Northeast, respectively. Efforts should be made to minimize gaps in care, emphasize importance of therapy, and provide adherence support.